The Effect of Ultrasound on the Rehydration Characteristics of Semi-Dried Salted Apostichopus japonicus - Wang, Xiaoyan; Su, Yongchang; Wang, Yangduo; Chen, Xiaoting; Chen, Xiaoe; Liu, Zhiyu (Foods, 2023)
To effectively shorten the rehydration time of Apostichopus japonicus and reduce the nutrient loss during the rehydration process, an ultrasound-assisted rehydration method was adopted to rehydrate semi-dry salted A. japonicus in this study. The effects of different ultrasonic powers, temperatures, and times on the rehydration characteristics, textural characteristics, and sensory quality of the semi-dry salted A. japonicus were studied. Box–Behnken response surface analysis was used to study the influence of the interactions among the three factors on the rehydration ratio of the semi-dry salted A. japonicus, and a quadratic multinomic regression model was established to predict the optimal rehydration ratio. The results showed that ultrasound could change the structure of semi-dry salted A. japonicus and form a spatial network structure, thereby improving its water absorption capacity and reducing rehydration time. The optimal rehydration effect could be obtained when the ultrasonic power was 400 W, the ultrasonic temperature was 50 °C, and the ultrasonic time was 83 min. Ultrasonic power, ultrasonic time, and ultrasonic temperature influenced the rehydration ratio of the semi-dry salted A. japonicus. Under the optimal rehydration conditions in this study, the rehydration ratio of semi-dry salted A. japonicus obtained by the test was 2.103, which was consistent with the value predicted by the Box–Behnken response surface method.